2002
DOI: 10.1002/ajh.10054
|View full text |Cite
|
Sign up to set email alerts
|

Frequent occurrence of anticardiolipin antibodies, Factor V Leiden mutation, and perturbed endothelial function in chronic myeloproliferative disorders

Abstract: Chronic myeloproliferative disorders (MPD) are characterized by a high incidence of thrombohaemorrhagic complications, possibly related to platelet abnormalities and disturbances of the coagulation system. In an attempt to de®ne abnormalities in coagulation and ®brinolysis, we investigated risk markers for venous thromboembolism, ®-brinolytic, and haemostatic system activation markers and antiphospholipid antibodies in blood samples from 50 MPD patients and 30 controls. Compared with controls median levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…The frequency of genetic thrombophilic factors, such as factor V Leiden or prothrombin mutations, was higher in MPN with venous thrombosis, suggesting that these tests should be performed in younger patients with a familial or personal history of thrombosis. [65][66][67] On the contrary, in regard to the role of antiphospholipid antibodies 68,69 and hyperhomocysteinemia, 70,71 data so far produced are too limited to recommend their evaluation in the work-up of patients with MPN.…”
Section: Other Risk Factorsmentioning
confidence: 99%
“…The frequency of genetic thrombophilic factors, such as factor V Leiden or prothrombin mutations, was higher in MPN with venous thrombosis, suggesting that these tests should be performed in younger patients with a familial or personal history of thrombosis. [65][66][67] On the contrary, in regard to the role of antiphospholipid antibodies 68,69 and hyperhomocysteinemia, 70,71 data so far produced are too limited to recommend their evaluation in the work-up of patients with MPN.…”
Section: Other Risk Factorsmentioning
confidence: 99%
“…Various studies showed that carrier frequency of The prothrombin G20210A polymorphism in healthy southern europeans was around 3 % (Rosendaal et al Bykowska et al 2000), nearly twice as high as data from the north of Europe (Poort et al 1996;Rosendaal et al 1998;Jensen et al 2002).…”
Section: Discussionmentioning
confidence: 98%
“…The largest study of 304 ET and PV patients identified an association between presence of the factor V Leiden mutation and venous thrombosis (16%) compared with its absence (3%). 30 An increased prevalence of antiphospholipid antibodies has been reported in ET 31,32 and correlated with thrombosis in one report. 31 Small sample sizes and limited confirmatory testing of the detected antibodies limit the impact of these findings.…”
Section: Risk Factors For Thrombosismentioning
confidence: 91%